PC CARD SONY ERICSSON: SEMIOTIK DAN IKLAN - Yulia Mutmainnah (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2014)
Through advertisement, producers send messages for their product strength to consumers. Those messages are conveyed through various kinds of signs either in the form of language, picture, caption, icon, index, or symbol. There is communicative exchange on GC79 PC Card Sony Ericsson advertisement between sender and receiver. Sender (advertisement maker) of this advertisement makes good use of reward polluter style, which is, persuading comsumers to use PC Card Sony Ericsson product.Keywords: advertisement, sender, receiver, signs, communication act.